DIFFERENCES OF PROPORTION OF DISTRACTORS NUMBERS OF ECONOMIC QUESTION ITEM FOR SENIOR HIGH SCHOOL GRADE 11 IN BEKASI CITY - Raden Roro Ernawati (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2019)
The purpose of this research to measure the comparation of distractors proportion number in economic question. This research was an experiment in a senior high school in Bekasi. The sample of the research was obtained technically cluster random sampling. Data was analyzed by using one way analyzed of variance (ANOVA) 3 x 1 treatment by level design. The results of this research is rejected hypothesis based on ANOVA number significant (0.127) higher than degree freedom (0.005). The conclution is distractors  proportion two, distractors  proportion three, and distractors  proportion four have same proportion thatâ€™s no different absolutely. The  results of the reseach recommended that the teacher used distractors two, distractors three, and distractors four in the learning process.and paid attention to teacher competency for the readiness of student.